Audit Committee Effectiveness, Internal Audit Function and Financial Reporting Lag: Evidence from Malaysia - Ismail, Rohaida; Mohd-Saleh, Norman; Yakob, Rubayah (Asian Academy of Management Journal of Accounting and Finance, 2022)
This study examines the association among the effectiveness of audit committee, arrangement of internal audit function (IAF), and financial reporting lag (FRL). It also expands the literature by exploring the effect of IAF sourcing arrangement on financial reporting lag. Financial reporting lag is measured based on the number of days between the dates of the financial year end to the date of announcement of financial reporting. The effectiveness of the audit committee consists of size, independence, meetings, experts, and the chairperson’s qualifications. The internal audit arrangement is either performed in-house or outsourced to a third-party internal audit service provider and the cost of incurred for the IAF in the financial year. The agency theory is applied to explain the framework of this study and tested on 2,284 Malaysian listed companies from 2012 to 2015. Results show that IAF sourcing arrangement and cost are significantly associated with financial report lag. These findings offer important implications on audit committee and IAF literature through improving the timeliness of financial information.